(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
In this article, the objective state of sports theory is explained as a social phenomenon of the sphere of human activity, the system of conducting and organizing competitions, high sports results and victories in competitions, thereby strengthening health and conducting training sessions with the aim of general physical development of a person, being considered processes and manifestations of sports activities.